2005
DOI: 10.1002/ejlt.200401021
|View full text |Cite
|
Sign up to set email alerts
|

A first pilot study to produce a food antioxidant from sunflower seed shells ( Helianthus annuus )

Abstract: A first pilot study to produce a food antioxidant from sunflower seed shells (Helianthus annuus)This article explains a laboratory procedure to produce an antioxidant from grinded, dehulled and partially defatted sunflower seeds. Initially, a solvent suitable to extract phenols was searched among different solutions of water mixed with ethanol, methanol and acetone at 40% (vol/vol) (each tested at pH 5, 7 and 9). Both the ethanol/water 60:40 (vol/vol) and the acetone/water 60:40 (vol/vol) mixtures proved to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 22 publications
3
37
0
2
Order By: Relevance
“…Irrespective of CGA, SFM contains other phenolic compounds such as caffeic, rosmarinic and ferulic acids, as well as myricetin and rutin, all these compounds present in quantities of less than 0.15 ppm. De Leonardis et al (2005; reported that phenolic compounds of SFS included seven molecules like chlorogenic, caffeic, protocatechuic, o-cinnamic, ferulic and syringic acids. CGA is a phytochemical molecule which is the ester of caffeic acid (CA) and quinic acid (QA).…”
Section: Anti-nutritional Factors Of Sfmmentioning
confidence: 99%
“…Irrespective of CGA, SFM contains other phenolic compounds such as caffeic, rosmarinic and ferulic acids, as well as myricetin and rutin, all these compounds present in quantities of less than 0.15 ppm. De Leonardis et al (2005; reported that phenolic compounds of SFS included seven molecules like chlorogenic, caffeic, protocatechuic, o-cinnamic, ferulic and syringic acids. CGA is a phytochemical molecule which is the ester of caffeic acid (CA) and quinic acid (QA).…”
Section: Anti-nutritional Factors Of Sfmmentioning
confidence: 99%
“…Peanut hulls (skins) are a particularly rich source of phenolics, containing tannins, procyanidins, catechin and epicatechin oligomers, resveratrol, and other phenolic substances (KARCHESY & HEMMINGWAY 1986). Sunflower seed shells are rich in chlorogenic acids; caffeic acid can be isolated from the aqueous-ethanolic extract after saponification (DELEONARDIS et al 2005). Hazelnut hulls contain high concentrations of phenolics (MOURE et al 2003).…”
Section: Antioxidants Present In Oilseed Shells and Husksmentioning
confidence: 99%
“…The antioxidant compounds are present in both sunflower oil and oilseed-extracted meal [5]. Extracts with high antioxidant activity may also be obtained from sunflower seed shells [6,7]. Compared to vegetables oils, sunflower oil is especially rich in a-tocopherol [5].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to vegetables oils, sunflower oil is especially rich in a-tocopherol [5]. The antioxidant potential of defatted sunflower meal and sunflower seed shells is determined mainly by the content of phenolic compounds [5,6]. However, it has to be mentioned that shells contain only 0.7-5.4 % of sunflower seed phenolics, whereas the rest is located in kernels [8].…”
Section: Introductionmentioning
confidence: 99%